A Review on Sentiment and Emotion Analysis for Computational Literary Studies - Makhdom, Nasrullah; Verma, H N; Yadav, Arun Kumar (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
In sentiment analysis, emotions refer to the subjective feelings expressed in a text or speech that can be classified as positive, negative or neutral. Emotions are an important aspect of sentiment analysis because they provide insights into the attitudes, opinions and behaviors of individuals toward a particular topic or entity. The emergence of digital humanities has allowed for a more computational approach to understanding emotions in literature. The passage provides an overview of existing research in this area and understanding the emotionality involved in  text. Throughout this survey, it has been demonstrated that sentiment and emotion analysis is increasingly attracting attention within the field of digital humanities, particularly in computational literary studies.
Keywords: Sentiment Analysis; Emotion Analysis; Digital Humanities; Computational Literature; Opinion Mining